SONG AND MOTION AS METHOD IN INTRODUCING VOCABULARY IN ENGLISH (NUMBER AND COLOUR) AT EARLY CHILDHOOD - Ratna Purwanti (Universitas Bengkulu, 2021)
Early childhood is the first foundation for development, one of the children development such as language skill, especially in English. With the aim that children can compete in the global world when they grow up. However, the problem that occurs in the field, the English language is rarely taught as an introduction to their language skill, due to the lack of knowledge of English learning methods in the ability to speak right for children. However, there is one kindergarten that uses song and motion method to introduce English vocabulary. This study aims to explore the description of Song and motion as a method in introducing vocabulary (number and colour) in English at one of the kindergartens in central Banjarmasin. The researcher applied a descriptive qualitative design to explore Song and motion method to introduce vocabulary in English (number and colour). This study involved 15 children in Group B. The finding from this study revealed that the song and motion method is very beneficial for children English vocabulary, children can remember the vocabulary about number and colour in English and also children happily singing while moving. This study might be used as an input for a teacher to create learning English in the classroom.